The deposition, characterisation and biocompatibility of hydroxyapatite and silicon doped hydroxyapatite thin film coatings for orthopaedic applications - Coe, Samuel C. (2008)
Silicon doped hydroxyapatite (SiHA) could be used as a thin film coating on load bearing bone implants to provide a bioactive layer enabling bone to form a direct bond with the implant/bone interface thus increasing implant lifetime by lowering the chances of aseptic loosening. This study has been undertaken to investigate silicon additions to RF magnetron sputtered hydroxyapatite (HA) thin films. Detailed characterisation was carried out on SiHA thin films to establish the structural, chemical, mechanical and compositional properties. Silicon content was altered by adjusting the power density applied to silicon targets in a co-deposition process resulting in SiHA films containing 0.0, 1.8, 4.2 and 13.4 wt.% silicon. All as-deposited thin films were found to be amorphous. After annealing at 600˚C in flowing argon for 2 h, it was found that films exhibited a single phase HA structure. The addition of silicon inhibited HA crystallite growth and acted to lower the stability of HA films in aqueous solutions. The 13.4 wt.% SiHA thin film did not recrystallise until a heat treatment at 800˚C.